Nutritional, Hypoglycemic, and Haematinic Potentiality of Edible Mushroom Pleurotus tuber-regium (Rumph. ex Fr.) Singer - Sukumar Dandapat; Manoj Kumar; Rakesh Ranjan; Manoranjan Prasad Sinha (Journal of Tropical Life Science, 2019)
Mycochemical composition, calorific value, the antioxidant activity of Pleurotus tuber- regium was analyzed and impact of P. tuber- regium extract on rat model especially glycemic, vitamins and blood parameters were explored to validate its medicinal importance. Mycochemical screening showed the presence of biochemicals such as phenols, flavonoids, proteins, carbohydrates etc. The extract showed good antioxidant activity (33.62% total antioxidant activity equivalent to 21.30 µg ascorbic acid). The extract showed dose -dependent hypoglycaemic activity by significant decreased average blood glucose level at high dose (100.62 ± 1.04mg/dL) compare to control (124.40 ± 1.45 mg/dL), haematinic activity by elevation of hemoglobin (14.75 ± 0.24 g/dL) at a high dose of extract compared to control (11.66 ± 0.21 g/dL). P. tuber-regium extract elevated vitamin B12 of rats at high dose of extract (449.60 ± 3.12 pg/mL) compared to control (420.00 ± 2.86pg/mL). P. tuber-regium extract showed a positive response to hypoglycemic, haematinic, and vitamin level of the body and posses high calorific value. Hence P. tuber-regium can be used as good fodder, medicinal and nutritional supplement.